RETRACTED ARTICLE: Palmitoyl transferases act as novel drug targets for pancreatic cancer - Zhiqing Lin; Ziru Lv; Xin Liu; Keke Huang (Journal of Translational Medicine, 2023)
Abstract Background Pancreatic adenocarcinoma (PAAD) is one of the most leading causes of cancer-related death across the world with the limited efficiency and response rate of immunotherapy. Protein S-palmitoylation, a powerful post-translational lipid modification, is well-known to regulate the stability and cellular distribution of cancer-related proteins, which is mediated by a family of 23 palmitoyl transferases, namely zinc finger Asp-His-His-Cys-type (ZDHHC). However, whether palmitoyl transferases can determine tumor progression and the efficacy of immunotherapy in PAAD remains unknown. Methods Bioinformatics methods were used to identify differential ZDHHCs expression in PAAD. A systematic pan-cancer analysis was conducted to assess the immunological role of ZDHHC3 using RNA sequencing data from The Cancer Genome Atlas database. In vivo Panc 02 subcutaneous tumor model validated the anti-tumor effect of knockdown of ZDHHC3 or intraperitoneal injection of 2-bromopalmitate (2-BP), a typical broad-spectrum palmitoyl transferases inhibitor. Furthermore, we explored therapeutic strategies with combinations of 2-BP with PD-1/PD-L1-targeted immunotherapy in C57BL/6 mice bearing syngeneic Panc 02 pancreatic tumors. Results ZDHHC enzymes were associated with distinct prognostic values of pancreatic cancer. We identified that ZDHHC3 expression promotes an immunosuppressive tumor microenvironment in PAAD. 2-BP suppressed pancreatic-tumor cell viability and tumor sphere-forming activities, as well as increased cell apoptosis in vitro, without affecting normal human pancreatic ductal epithelial cells. Furthermore, genetic inactivation of ZDHHC3 or intraperitoneal injection of 2-BP impeded tumor progression in Panc 02 pancreatic tumors with enhanced anti-tumor immunity. 2-BP treatment significantly enhanced the therapeutic efficacy of PD-1/PD-L1 inhibitors in Panc 02 pancreatic tumors. Conclusion This study revealed some ZDHHC enzyme genes for predicting the prognosis of pancreatic cancer, and demonstrated that ZDHHC3 plays a critical oncogenic role in pancreatic cancer progression, highlighting its potential as an immunotherapeutic target of pancreatic cancer. In addition, combination therapy of 2-BP and PD-1/PD-L1 achieved synergic therapy effects in a mouse model of pancreatic cancer.